Localization in vehicle networks using radio frequency identification technology - M’Tumbe, T. A. (ХНУРЕ, 2020)
The incorporation of electronic systems of objects including sensor nodes, communication platforms and interactive objects in the domain of IoT are explored. The use of Radio Frequency Identification (RFID) in road transport includes speed monitoring automatically and access to data to get information, as well as vehicle detection in dense urban areas and in underground tunnels. The localization of vehicle using RFID in traffic that provides the position of the vehicle to present the identity and all information automatically has been investigated. The vehicle can obtain data from different positions with enabling RFID technologies. The multiple advantages are visible in these current fields where RFID technology is used.
Локалізація в автомобільних мережах з використанням технології радіочастотної ідентифікації